Spectrum of Multiorgan Dysfunction in Scrub Typhus Infection. (2nd September 2021) - Mahajan, Vidushi; Guglani, Vishal; Singla, Nidhi; Chander, Jagdish
Abstract: Objectives: We planned this study to determine the clinical spectrum and compare incidence of multiorgan dysfunction in children hospitalized with scrub typhus with other etiologies of tropical fever. Design: Prospective cohort study. Setting: Pediatric emergency and PICU services of a university teaching hospital situated in the sub-Himalayan region. Patient: Children aged 2 months to 14 years with acute undifferentiated fever of more than 5 days. Interventions: Detailed fever workup was performed in all children. We compared scrub typhus IgM positive children (cases) with remaining febrile children who were negative for scrub IgM assay (controls) for mortality and morbidity. Main results: We enrolled 224 febrile children; 76 children (34%) were positive for scrub typhus IgM ELISA. Scrub typhus group had a significantly higher incidence of multiorgan dysfunction [OR 3.5 (95% CI 2.0–6.3); p < 0.001] as compared to non-scrub typhus group requiring supportive care. The incidence of altered sensorium [OR 8.8 (95% CI 3.1–24.9)], seizures [OR 3.0 (95% CI 1.1–8.3)], acute respiratory distress syndrome [OR 17.1 (95% CI 2.1–140.1)], acute renal failure (5% vs. 0%), meningitis [OR 6.2 (95% CI 1.2–31.6)], thrombocytopenia [OR 2.8 (95% CI 1.5–5.1)], transaminitis [OR 2.7 (95% CI 1.6–4.8)], requirement of oxygen [OR 17.8 (95% CI 4.0–80.3)], positive pressure support [OR 3.7 (95% CI 1.2–10.5)] and shock requiring inotropes [OR 3.0 (95% CI 1.3–6.7)] was significantly higher in scrub typhus group as compared to the non-scrub typhus group (Table 1). Conclusions: Pediatric scrub typhus who were hospitalized had severe systemic manifestations when compared to other causes of fever.